Developing flexible-adaptive reasoning and computing - Brocardo, Joana (2018)
The project ‘Numerical thinking and flexible calculation: critical issues’ aims to study students’ conceptual knowledge associated with the understanding of the different levels of learning numbers and operations. We follow the idea proposed by several authors that flexibility refers to the ability to manipulate numbers as mathematical objects which can be decomposed and recomposed in multiple ways using different symbolisms for the same objet (Gravemeijer, 2004; Gray &Tall, 1994;). The project plan is based on a qualitative and interpretative methodology (Denzin & Lincoln, 2005) with a design research approach (Gravemeijer & Cobb, 2006). This article focus the preparation of a teaching experience centered in the flexible learning of multiplication. It describes the analysis of a clinical interview where Pedro (9 years) solves the task 'Prawn skewers'. It illustrates how we identify and describe Pedro’s conceptual knowledge associated with the different levels of understanding of numbers and multiplication/division and analyzes if and how this knowledge facilitates adaptive thinking and flexible calculation.